THE EFFECT OF NUMBER ON AXILLARY BUDS ON THE SURVIVAL RATE AND GROWTH OF CUTTING OF FOUR MULBERY HYBRID - Aris Sudomo; Sugeng Pudjiono; Mohamad Na'iem (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2007)
The study aimed to examine the effect of number of axillary buds on different types of mulberry hybrid and their interaction on the survival rate and cutting growth. The research was conducted using Random Design of Factorial Group (RDFG). It consists of two treatment factors, i.e. four type of mulberry hybrid (M. SHA 4 x M. LUN 109, M. multicaulis x M. indica, M. australis x M. indica, M. nigra x M. indica) and four different numbers of axillary buds with 3 replications and 30 replicates for each unit experiment. The research shows that there were effect of axillary bud number, types of mulberry hybrid, and their interaction on the survival rate and growth of stem cutting of mulberry hybrid. The number of axillary bud for the best growth of stem cutting of mulberry hibrid for the best sprout length of cutting and the highest survival percentage (81, 668%) was the 3 axillary buds, while the 4 buds was the best according to the rank of whole parameter. The best cutting type of mulberry hybrid according to the rank of whole parameter was M. australis x M. indica. Interaction beetwen mulberry hybrid and the best sprout number according to the rank of whole parameter was M. australis x M. indica with 4 sprout number.